2009
DOI: 10.4103/0019-5413.54969
|View full text |Cite
|
Sign up to set email alerts
|

Limb conservation in extremity soft tissue sarcomas with vascular involvement

Abstract: Background:The major neurovascular involvement and large primary tumors are indication of amputation. The present study is an attempt to explore the feasibility of a limb salvage surgery in extremity sarcoma cases with major vessel involvement. Oncological outcomes and surgery-related morbidities are compared with those reported in literature.Materials and Methods:A retrospective review of all limb salvage surgeries done in our department between 2005 and 2008 was done and four cases of extremity sarcoma of lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…[1,5,11,12,19,20] In malignant tumors, common indications for amputation are major neurovascular involvement and large primary tumor where resection would leave a functionally useless limb. [21] In our study, there were involvements of femoral artery-vein in case 5 and of medial collateral ligament in case 7. There was low malignancy risk for both cases according to risk stratification model.…”
Section: Discussionmentioning
confidence: 88%
“…[1,5,11,12,19,20] In malignant tumors, common indications for amputation are major neurovascular involvement and large primary tumor where resection would leave a functionally useless limb. [21] In our study, there were involvements of femoral artery-vein in case 5 and of medial collateral ligament in case 7. There was low malignancy risk for both cases according to risk stratification model.…”
Section: Discussionmentioning
confidence: 88%
“…Thus, en bloc resection is the mainstay of treatment for sarcomas involving blood vessels, to achieve negative margins and reduce local recurrence. Many studies have reported local recurrence rates of 14% to 47% [ 1 , 5 , 19 ]. Fortunately, there were no local recurrences in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…2 The femoral artery is commonly replaced with an autologus reversed saphenous vein graft because of its resistance to infections and its excellent patency rates 2-4 compared with artificial grafts. 4,5 We present a case of thigh sarcoma involving the femoral vascular axis with complete clogging of the femoral vein due to massive deep thrombosis. The video illustrates the features of the case and highlights the steps of a wide compartment resection with arterial reconstruction by autologus reversed saphenous vein graft.…”
Section: -3mentioning
confidence: 99%